Genetic and functional analyses detect an EXT1 splicing pathogenic variant in a Chinese hereditary multiple exostosis (HME) family. Issue 3 (1st February 2022) - Li, Jianwei; Wang, Zhiqiang; Han, Yaxin; Jin, Chengfang; Cheng, Dalin; Zhou, Yong‐An; Zhen, Junping
Abstract: Background: Hereditary multiple exostosis (HME) is an autosomal dominant skeletal disorder characterized by the development of multiple cartilage‐covered tumors on the external surfaces of bones (osteochondromas). Most of HME cases result from heterozygous loss‐of‐function mutations in EXT1 or EXT2 gene. Methods: Clinical examination was performed to diagnose the patients: Whole exome sequencing (WES) was used to identify pathogenic mutations in the proband, which is confirmed by Sanger sequencing and co‐segregation analysis: qRT‐PCR was performed to identify the mRNA expression level of EXT1 in patient peripheral blood samples: minigene splicing assay was performed to mimic the splicing process of EXT1 variants in vitro. Results: We evaluated the pathogenicity of EXT1 c.1056 + 1G > T in a Chinese family with HME. The clinical, phenotypic, and genetic characterization of patients in this family were described. The variant was detected by whole‐exome sequencing (WES) and confirmed by Sanger sequencing. Sequencing of the RT‐PCR products from the patient's blood sample identified a large deletion (94 nucleotides), which is the whole exome 2 of the EXT1 cDNA. Splicing assay indicated that the mutated minigene produced alternatively spliced transcripts, which cause a frameshift resulting in an early termination of protein expression. Conclusions: Our study establishes the pathogenesis of the splicing mutation EXT1 c.1056 + 1G > T to HME and provides scientific foundation for accurate diagnosis and precise medical intervention for HME. Abstract : Our study establishes the pathogenesis of the splicing mutation EXT1 c.1056 + 1G > T to hereditary multiple exostosis and provides scientific foundation for accurate diagnosis and precise medical intervention for HEM.